Estudo da adsorção da cadaverina e putrescina em nanotubos de carbono, nitreto de boro e nitreto de gálio utilizando a teoria funcional da densidade - FERREIRA, Francisco Gleidson de Sousa (2020)
This work presents a theoretical study about Carbon nanotubes, Boron Nitride (BN) and Gallium Nitride (GaN) interacting with the molecules of cadaverina and putrescina through simulations of first principles, based on the theory of density functional. The simulation calculations were made using the computer program SIESTA. The structural, energetic and electronic properties of the cadaverine and putrescine molecules adsorbed on the nanotubes were analyzed. The results show that the electronic properties are affected by the interaction of the molecules and that there is a decrease in the gap value, in pure BN the gap was 3,92 eV, when it interacts with putrescina it has a gap of 3,87 eV and with cadaverina the gap increased to 3,65 eV. The gap of pure GaN was 2,32 eV, changed to 2,25 eV with putrescina and 2,28 eV with cadaverina. For the pure carbon nanotube and with the molecules, there was no change in the gap, this being 0,63 eV. The calculations also indicate that both adsorbed molecules interact with the surface of the carbon nanotube and BN through physical adsorption and on the surface of GaN through chemical adsorption.